Step-by-step explanation:
Hey there!
Distance = 12x^2+11x+2.
And Time = 3x+2 hours.
Now;
Putallvalues.
Usemidtermfactorizationisnumeratorandsimplifythemtogetanswer.
Therefore thespeedis(4x+1)/hr.
Hopeit helps..
Answer:c=35
Step-by-step explanation:
B. 40
C. 31
D. 20
E. 4
Calculating the value of f(x) for the given interval.
For x = - 4, f(x) = f(- 4) = (- 4)^2 + 2 (- 4) + 3 = 11
For x = 6, f(x) = f(6) = (6)^2 + 2 (6) + 3 = 51
Now using formula for the calculation of average rate of change of f(x) over the given interval of [- 4, 6];
(f(b) – f(a)) / b – a = (f(6) – f(- 4)) / 6 – (- 4) = (51 -11) / 10 = 4
So option “E” is correct.
Answer:
First question:
The graph of has a vertical asymptote at x = and a horizontal asymptote at y =
Second question:
The graph of equation has a horizontal asymptote at y = -3 ⇒ C
Step-by-step explanation:
The vertical asymptotes will occur at the values of x for which make the denominator is equal to zero
The horizontal asymptotes will occur if:
First question:
∵
- To find the vertical asymptote equate the denominator by 0
to find the value of x
∵ The denominator is 2 - 3x
∴ 2 - 3x = 0
- Add 3x to both sides
∴ 2 = 3x
- Divide both sides by 3
∴ = x
∴ The graph has a vertical asymptote at x =
To find the horizontal asymptote look at the highest degree of x in both numerator and denominator
∵ The denominator and the numerator has the same degree of x
- Divide the coefficient of x of the numerator and denominator
∵ The coefficient of x in the numerator is -2
∵ The coefficient of x in the denominator is -3
∵ -2 ÷ -3 =
∴ The graph has a horizontal asymptote at y =
The graph of has a vertical asymptote at x = and a horizontal asymptote at y =
Second question:
The graph has a horizontal asymptote at y = -3
means the numerator and the denominator has same highest degree and the coefficient of the highest degree in the numerator divided by the coefficient of the highest degree in the denominator equal to -3
∵ In answer A the quotient is 1 because x up and down have
coefficient 1
∵ In answer B the quotient is because the coefficient of x
up is 1 and down is -3
∵ In answer D the quotient is -1 because the coefficient of x
up is 3 and down is -3
∵ In answer C the quotient is -3 because the coefficient of x up
is -3 and down is 1
∴ The graph of equation has a horizontal asymptote at y = -3